2018
DOI: 10.1093/jeea/jvy013
|View full text |Cite
|
Sign up to set email alerts
|

Politics in the Courtroom: Political Ideology and Jury Decision Making

Abstract: This paper uses data from the Gothenburg District Court in Sweden and a research design that exploits the random assignment of politically appointed jurors (termed nämndemän) to make three contributions to the literature on jury decision-making: (i) an assessment of whether systematic biases exist in the Swedish nämndemän system, (ii) causal evidence on the impact of juror political party on verdicts, and (iii) an empirical examination of the role of peer effects in jury decisionmaking. The results reveal a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 39 publications
(23 reference statements)
1
19
0
Order By: Relevance
“…10 Taken as a whole, the results of our analysis imply that female representation on juries substantially affects the likelihood of conviction for a subset of cases -sexual and violent crimes -in which female jurors might have viewed the alleged behavior or its impact on the victim from a different perspective than their male counterparts. While the present study is based on data from nearly a century ago, the magnitude of the results raises concerns about 10 These results are broadly consistent with results reported for Sweden in Anwar, Bayer, and Hjalmarsson (2015), which finds that lay judges (nämndemän) from the feminist Vänster party are significantly more likely to convict defendants when the victim of violent crime is female. Criminal trials in Sweden are decided by a judge and three nämndemän, who are nominated by political parties in proportion to the party's performance in the most recent election.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…10 Taken as a whole, the results of our analysis imply that female representation on juries substantially affects the likelihood of conviction for a subset of cases -sexual and violent crimes -in which female jurors might have viewed the alleged behavior or its impact on the victim from a different perspective than their male counterparts. While the present study is based on data from nearly a century ago, the magnitude of the results raises concerns about 10 These results are broadly consistent with results reported for Sweden in Anwar, Bayer, and Hjalmarsson (2015), which finds that lay judges (nämndemän) from the feminist Vänster party are significantly more likely to convict defendants when the victim of violent crime is female. Criminal trials in Sweden are decided by a judge and three nämndemän, who are nominated by political parties in proportion to the party's performance in the most recent election.…”
Section: Introductionsupporting
confidence: 81%
“…Given that previous work has shown that the impact of jurors can depend on victim gender (Anwar, Bayer, and Hjalmarsson, 2015), Table 7 looks directly at whether there was a differential effect of the reform on convictions for cases with at least one female victim. We restrict this analysis to violent offenses, as the classification of victim gender is the most straightforward for these cases: almost all violent offenses have a male or female victim.…”
Section: Begins In Columnmentioning
confidence: 99%
“…Each district court also maintains a large pool of politically appointed lay jurors (nämndemän) that serve a similar function as juries in the American system. Each lay juror works approximately 10 to 15 days per year, with essentially random assignment of the lay jurors to both cases and judges (Anwar, Bayer and Hjalmarsson 2019 In most district court trials, both the verdict and sentence are decided by both the judge and the three lay jurors. Following the hearing, the judge summarizes the facts of the case and any relevant laws for the three lay jurors.…”
Section: A the Swedish Court Systemmentioning
confidence: 99%
“…Finally, the court coordinator assigns each juror triplet to a courtroom scheduled to be in session in a quasi-random fashion. See Anwar, Bayer and Hjalmarsson (2019) for additional details on lay jurors in Sweden. 7 There are 32 local prosecution offices in Sweden.…”
Section: A the Swedish Court Systemmentioning
confidence: 99%
“…Besides the lack of data availability and severe restrictions on data use (see e.g. for data issues of jury trial data Anwar et al, 2015), a major problem for the empirical analysis is the endogeneity of the selection procedure, as different groups tend to adopt different institutional arrangements. The causal effect of endogenous institutional choice cannot be disentangled from the characteristics of the individuals who make the choice and the profile of the person in charge of administering sanctions.…”
Section: Introductionmentioning
confidence: 99%